Kemampuan Kognitif Siswa Kekas VIII A dalam Menyelesaikan Soal Matematika Materi Persamaan Linear Satu Variabel - Ghello, Dion; Making, Samuel Rex Mulyadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the cognitive abilities of class VIII A students in solving mathematics problems on the material of Single Variable Linear Equations (PLSV) based on the Revised Bloom's Taxonomy indicators. The study used a qualitative approach with descriptive methods. The research subjects were 17 class VIII A students of SMP Negeri 1 Loura who were determined using a total sampling technique because all students in the class were used as research subjects. Data were collected through essay tests, observation, and documentation. The test instrument consisted of six questions representing cognitive ability indicators C1 (remembering), C2 (understanding), C3 (applying), C4 (analyzing), C5 (evaluating), and C6 (creating). Data were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing, and supported by percentage analysis to group the level of students' cognitive abilities. The results showed that students' cognitive abilities were in the high category, with 29.4% of students in the very high category, 58.8% in the high category, and 11.8% in the medium category. Difficulties were still found in higher-order thinking skills, particularly in the analysis, evaluation, and creation indicators. This finding indicates the need for implementing learning strategies that are more oriented toward developing higher-order thinking skills as the basis for developing learning and evaluation in PLSV materials